PENGARUH BAURAN PEMASARAN JASA TERHADAP LOYALITAS PELANGGAN DI TAMAN AIR PANAS DARAJAT PASS - Aripin Setiawardi; M Ali Ramdhani; Andri Ikhwana (Jurnal Kalibrasi, 2013)
This research was made to understandand analyze how big is the influence of marketing mix service toward customer loyalty using tourist service Taman Air Panas Drajat Pass. A method used in this research about the influence of marketing mix service toward customer loyalty arefield observation method, interview, questionnaire, and literature study using liker scale. In samle determination, the writer usedaccidental sampling method for about 90 samles whereas the approximation method used in data analysis methodis Linearregression method which has the function to know the relationship between independent variable, that is marketing mix (X) with dependent variable, that is customer loyalty (Y). The research showed us that marketing mix consist of: product (X1), price (X2), place (X3), promotion (X4), physical evidance (X5), people (X6),and (x7) simultaneously has a significant. Effect toward customer loyalty (Y). But partially, the one who has a significant effect toward customer loyalty is variableprocess with the significantlevel that is 0,017. This marketing mix can expalin that customer loyalty of Taman Air Panas Darajat Pass is 0,356 or 35,6% while the rest of it, that is 64,4% is the customer loyalty that has not been explained by customer’s attitude, purchasing conviction variable, evaluation variable normative conviction variable and motivation variable.